Prospects of industrial and innovative development of the economy of Kazakhstan in modern conditions - Muratova, R.A.; Mukhametzhanova, Zh.S.; Kurbanova, K.A.; Mukhametzhanova, Zh.S. (BUKETOV BUSINESS REVIEW, 2020)
Object: Industrial and innovative development of the economy of the Republic of Kazakhstan is a priority issue of all economic development. State regulation of the economy purposes at strategic objects and problems formulation for perspective development. Methods: The article presents data on the volume of industrial production, the physical volume indices for manufacturing industries are considered. The trends and levels of technological industrialization of manufacturing industries are considered separately. Findings: The trends and forms of the manufacturing industry’s development of the Republic of Kazakhstan in the sectoral and regional section are considered. Priority orientations of the industry development have been determined. The prospects for strategic planning are noted, and also the differentiation in the level of regional development. The dynamics of changes in the gross domestic product is considered and some prospects for the development of the manufacturing industry in terms of the development of petrochemical production are determined. Conclusions: The article formulation the issues of transformation to an export-oriented economy and defines the trends of development of real sector industries.